Correction: Design and Validation of a Periodic Leg Movement Detector. - Hyatt Moore; Eileen Leary; Seo-Young Lee; Oscar Carrillo; Robin Stubbs; Paul Peppard; Terry Young; Bernard Widrow; Emmanuel Mignot (PLoS ONE, 2015)
[This corrects the article DOI: 10.1371/journal.pone.0114565.].